Hilangnya Jaminan Fidusia dalam Perjanjian Kredit dan Konsekuensi Hukumnya - Dahris Siregar; Muhammad Dhobit Azhary Lubis (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2026)
The withdrawal of the fiduciary guarantee will be affected if the credit agreement's fiduciary guarantee object is destroyed or lost. The purpose of this research is to ascertain the legal implications of fiduciary pledges in credit agreements being lost by taking into account the position of creditors in such a scenario. The issues brought up, examined, and clarified in this study are centered on the application of rules or norms in positive law as it employs a normative research methodology. Primary, secondary, and tertiary legal materials are used in the issue method, which combines a legal and conceptual approach. The study's findings demonstrate that the legal ramifications of a fiduciary guarantee loss arrangement do not absolve the debtor of making the outstanding credit installment payments to creditors. According to the study's findings, fiduciary assurances in credit agreements are essential for providing creditors with legal protection. since the debtor is the object of the guarantees. This implies that should the debtor fail to fulfill their obligations under the credit agreement with fiduciary assurances, in order to ensure the interests of creditors are protected by the law, when attempting to reach a settlement, creditors may seek executorial seizure of the debtor's assets.